O ministério ordenado: aspectos histórico-teológicos. (Um esboço) - Taborda, Francisco (Revista Eclesiástica Brasileira, 2019)
Trata-se de esboçar a evolução histórica dos três ministérios ordenados. O episcopado passou de uma forma coletiva para o episcopado de um só. Na Idade Média, foi visto como mera “dignidade” até que o Vaticano II recupera a sacramentalidade do episcopado e sua colegialidade. Com a passagem do episcopado coletivo ao monepiscopado, o presbitério se torna o conselho do bispo. O crescimento da Igreja leva os presbíteros a assumirem a presidência da eucaristia por encargo do bispo; o coletivo se diluiu num grupo de indivíduos. O presbítero se torna o agente quase exclusivo da atuação eclesial e o presbiterado o ápice do sacramento da ordem. O Concílio de Trento consagra essa perspectiva. O Vaticano II redescobre o caráter colegiado do presbiterado. O ministério diaconal experimenta nos primeiros séculos uma ascensão que atinge seu apogeu nos séculos IV-VI. A partir de então, entra em rápido declínio a ponto de reduzir-se, na Igreja latina, a mero degrau para se alcançar o presbiterado. O Vaticano II restaura o diaconado como ordem permanente. Abstract: This paper is attempting to make an historical evolutionary outline of the three ordained ministries. The episcopal ministry passed from being a collective one to be defined to one person. In the Middle Ages, this was seen as a mere “dignity” up until Vatican II recuperated the sacramentality of the episcopate and its collegiality. With the change from a collective episcopate to being defined to a single personage, the presbyterium became but a counsel to the bishop. The Church’s growth leads these bishops to delegate the presidency of the Eucharist to the presbyters; the collective was diluted in a group of individuals. The presbyter becomes the quasi exclusive agent of Ecclesial action and the presbyterate becomes the apex of the sacrament of ordination. The Council of Trent consecrated this perspective. Vatican II rediscovers the collegial character of the presbyterate. The diaconal ministry experiences in the first centuries an increased until attains its apogee in the IVVI centuries. From that moment, it starts to rapidly decline to the point of becoming, in the Latin Church, a mere step towards the presbyterate. The Vatican II restores the diaconate as a permanent Holy Order. Keywords: Historical figure; Episcopate; Presbyterate; Diaconate.